2017
DOI: 10.5535/arm.2017.41.4.610
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neurophysiological Monitoring for Spinal Cord Tumor Surgery: Comparison of Motor and Somatosensory Evoked Potentials According to Tumor Types

Abstract: ObjectiveTo identify which combination of motor evoked potentials (MEPs) and somatosensory evoked potentials (SEPs) is most reliable for postoperative motor deterioration during spinal cord tumor surgery, according to anatomical and pathologic type.MethodsMEPs and SEPs were monitored in patients who underwent spinal cord tumor surgery between November 2012 and August 2016. Muscle strength was examined in all patients before surgery, within 48 hours postoperatively and 4 weeks later. We analyzed sensitivity, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(30 reference statements)
0
8
0
1
Order By: Relevance
“…So far, several studies have confirmed that surgery for spinal meningioma is a safe procedure and favorable long-term functional outcome can be achieved (4,5,10,14,29,30). However, the present series spans over a 19-year period and investigates the benign WHO grade I and II SMs, all of which were resected using MEP and SEP monitoring-an established tool in modern spinal tumor surgery (9).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…So far, several studies have confirmed that surgery for spinal meningioma is a safe procedure and favorable long-term functional outcome can be achieved (4,5,10,14,29,30). However, the present series spans over a 19-year period and investigates the benign WHO grade I and II SMs, all of which were resected using MEP and SEP monitoring-an established tool in modern spinal tumor surgery (9).…”
Section: Discussionmentioning
confidence: 90%
“…The typical clinical presentation at onset consists of pain followed by motor deficits, gait instability, and sphincter dysfunction (8). A milestone in the surgical management of spinal tumors was the introduction of intraoperative MEP and SEP monitoring to preserve neurological functions (9). Furthermore, it is suggested that anterior location, prolonged duration of baseline symptoms before surgery, WHO grade >I, and Simpson grade II and III resections are predictive factors of a poor functional outcome (10).…”
Section: Introductionmentioning
confidence: 99%
“…In surgeries for the removal of spinal cord tumors, a decrease in amplitude during SEP and MEP monitoring serves as an alarm criterion, and such an amplitude reduction has been found to be important in predicting postoperative motor deterioration. 1,4,7 This study aimed to determine the effect on motor status when the MEP amplitudes increased. In this study, we studied 115 In the analysis with Pearson coefficient configuration, there was a positive correlation between Motor 48h-pre and MEP min ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many spinal and brain surgeons now use MEP monitoring for their surgery, as it better predicts good postoperative motor outcomes than the use of SEPs alone. [7][8][9][10] In addition to this predictive power, MEP data recording benefits from a high temporal resolution; the data may be updated on the order of seconds, providing the surgeon with "real-time" information about possible surgical trauma.…”
mentioning
confidence: 99%
“…Multimodal monitoring with combination of MEPs and D waves has been recommended in SCT surgery for favorable long-term outcomes [1][2][3]. The sensitivity and specificity of the test used to predict postoperative motor deterioration in SCT surgery are known to be lower in SEPs than in MEPs [4][5][6]. According to a meta-analysis of eight studies on intramedullary SCT (IMSCT) surgery, the pooled sensitivity of SEPs was 85% (range, 70-95; 95% CI, 75-91) and specificity was 72% (range, 61-96; 95% CI, 57-83) [7].…”
Section: Introductionmentioning
confidence: 99%